Skilled and Unskilled Wages in a Globlizing World, 1968-1998 - CHOR, Davin (Institutional Knowledge at Singapore Management University, 2008)
This paper constructs a data set on purchasing-power-parity (PPP) adjusted skilled and unskilled wages in 139 countries for the period 1968-1998, based on the International La- bor Organization's (ILO) annual October Inquiry and the Freeman and Oostendorp (2000) Occupational Wages Around the World (OWW) le. It nds strong evidence for the ex- istence of well-integrated markets for skilled and unskilled labor, justifying the approach of constructing a skilled wage series and an unskilled wage series. Several signi cant re- sults emerged from an analysis of a representative subset of 67 countries which provided unbroken coverage for 1970-1994: (i) there is striking evidence of unconditional con- vergence in the skilled-unskilled wage ratio worldwide; (ii) this relative wage convergence was especially strong within a \club of open economies, suggesting that Heckscher-Ohlin- Sameulson mechanisms might be at work; and (iii) there is a relatively weak pattern of convergence in unskilled real wages, implying that the claim of \Divergence, Big Time (Pritchett 1997) has to be quali ed when factor markets are studied instead of aggregate incomes.